ANALYSIS OF FLAVONOID LEVELS AND TOTAL PHENOLICS FROM BUNGUR LEAF EXTRACT (Lagerstroemia speciosa) AGAINST ANTIOXIDANT ACTIVITY - Ernie Halimatushadyah; Agnes Yuliana (Jurnal Ilmiah Farmako Bahari, 2023)
The levels of flavonoids and total phenolics contained in the methanol, 70% ethanol, and ethyl acetate extracts of Bungur leaves (Lagerstroemia speciosa) will be reported in this study. In addition, the antioxidant activity of each extract was also tested. The Bungur leaves (Lagerstroemia speciosa (L) pers) is a plant used empirically as medicine. The preparation and preparation of the extract was carried out by the maceration method, which used three different variations of solvents, including methanol, 70% ethanol, and ethyl acetate. The type of coating and the polarity of the coating significantly affect the antioxidant activity obtained. The phytochemical screening test was carried out to determine the content of chemical compounds in plant extracts. In contrast, the control of flavonoid levels and total phenolic content was carried out using the colorimetric method. Measurement of antioxidant activity levels was carried out using the DPPH test. The qualitative phytochemical screening test results of the methanol, 70% ethanol, and ethyl acetate extracts had the same secondary metabolite content. Still, the highest total flavonoid and phenolic content were found in the methanol extract of Bungur leaves, 9.06% and 16.42%. The antioxidant activity test of the methanol extract of Bungur leaves also showed the best inhibition results, as indicated by the IC50 value of 5.76 ppm. This can strengthen the total phenol and flavonoid levels correlated with antioxidant activity.